How do the time-varying risk prices behave in Japan? An investigation with a multivariate GARCH-CAPM approach - Chikashi Tsuji (The Open Economics Journal, 2008)
This paper examines the pricing of month-by-month time-varying risks on the Japanese stock market over the period from 1981 to 2004. Using the multivariate GARCH model, we tested the conditional version of the Sharpe-Lintner-Mossin CAPM. In contrast to previous studies, we derive and focus strictly on the monthly time-varying risk prices while employing the Fama and French approach by constructing 25 size-ranked and 25 BE/ME-ranked portfolio returns. The empirical results show that the price of risk in the conditional version of the Sharpe-Lintner-Mossin CAPM is generally positive and significant when the time-varying covariances from the multivariate GARCH model are used. This provides evidence contrary to the findings of many international studies in which the validity of the traditional CAPM is very often denied.
Keywords: 330; conditional CAPM; multivariate GARCH model; time-varying risk aversion; time-varying risk price